2009
DOI: 10.1016/j.cpr.2009.01.005
|View full text |Cite
|
Sign up to set email alerts
|

The importance of functional impairment to mental health outcomes: A case for reassessing our goals in depression treatment research

Abstract: Outcomes in depression treatment research include both changes in symptom severity and functional impairment. Symptom measures tend to be the standard outcome but we argue that there are benefits to considering functional outcomes. An exhaustive literature review shows that the relationship between symptoms and functioning remains unexpectedly weak and often bidirectional. Changes in functioning often lag symptom changes. As a result, functional outcomes might offer depression researchers more critical feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
267
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(283 citation statements)
references
References 212 publications
(187 reference statements)
11
267
0
5
Order By: Relevance
“…In this study, whenever functional disability was present there was a 75% likelihood of a coexisting psychosocial disability being reported. Although the direction of causation is not clear, this would be expected to be bi-directional, as psychosocial disability is known to be a risk factor for functional impairment (McKnight and Kashdan, 2009), and functional impairment has been shown to increase vulnerability to psychosocial disability (Lenze et al, 2001). The high prevalence of psychosocial impairment potentially hides participation, access to services and barriers for those with functional disabilities.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, whenever functional disability was present there was a 75% likelihood of a coexisting psychosocial disability being reported. Although the direction of causation is not clear, this would be expected to be bi-directional, as psychosocial disability is known to be a risk factor for functional impairment (McKnight and Kashdan, 2009), and functional impairment has been shown to increase vulnerability to psychosocial disability (Lenze et al, 2001). The high prevalence of psychosocial impairment potentially hides participation, access to services and barriers for those with functional disabilities.…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of MDD treatment in relation to functional outcomes is potentially confounded by the bidirectional relationship of depressive symptoms and functional impairment, as well as by premorbid functioning, which may not be accounted for when assessing the reduction in functional impairment (McKnight & Kashdan, 2009). The National Comorbidity Survey Replication found that 96.9% of patients with MDD for at least 12 months also suffered from functional impairment (in at least one area) associated with their depression, with 19.1% of patients reporting their impairment as “very severe” (Kessler et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is probable that there is a bidirectional relationship between mental disorder and work disability. [38] The study was also limited by the single-centre design in specialised tertiary unit. It is possible that the results would be different in a less well-established service, or might vary geographically.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%